Force Matters of Negligence in Removing The Debtor's Liability In Civil Agreements - Hanim, Latifah; Wiranto, Agus Prasetia (UNISSULA Semarang, 2026)
This study aims to analyze the role of force majeure in eliminating debtors' responsibilities in civil agreements and examine the limitations of its application in legal practice in Indonesia. Force majeure is a condition beyond the capabilities and desires of the parties that causes performance to be unable to be fulfilled, thus having implications for the elimination of the debtor's compensation obligation. The main problem in this study is how the concept of force majeure is regulated in Indonesian civil law and the extent to which such conditions can be used as a basis for exempting debtors from their responsibilities. The research method used is normative legal research with a statutory and conceptual approach, which is analyzed qualitatively. The results show that force majeure has an important position as a justification that can exempt debtors from the obligation to pay compensation, as stipulated in the provisions of the Civil Code. However, not all circumstances can be categorized as force majeure; rather, they must meet certain elements such as being unpredictable, occurring beyond the debtor's fault, and being unavoidable. In practice, the interpretation of force majeure often gives rise to differences, especially in determining whether an event truly meets the criteria for force majeure. Therefore, it is necessary to have clearer legal parameters to ensure legal certainty and justice for the parties to the agreement.